Development of directed regulation of rheological properties of fire retardant composite materials of ethylene vinyl acetate copolymer - Chulieieva, Olena (Technology audit and production reserves, 2017)
The object of research is rheological processes of viscous flow of non-combustible polymeric composite materials. One of the most problematic issues arising in the processing of polymer composite materials is an increased viscosity, which requires an increase in shear stresses to achieve a given speed. In order to solve this problem, a method has been developed for the directed regulation of the rheological characteristics of polymer compositions by injecting a modifier into their composition. The influence of the modifier on the viscous flow processes of fire retardant materials of an ethylene with vinyl acetate copolymer and fire retardant fillers, has been studied. In the studies, an ethylene vinyl acetate copolymer is used. The content of vinyl acetate is 18 % and 28 %; MFI 2.5 g/10 min and MFI 5 g/10 min. Modifier is aminosilane. Fillers are fire retardants: aluminum trihydroxide with an average particle diameter of 1.5 μm and 3.0 μm; magnesium hydroxide with an average particle diameter of 3.0 μm and 3.7 μm; hydromagnesite with an average particle diameter of 1.4 μm. Using the method of capillary viscometry, the following characteristics are determined: melt flow index, shear stress, shear rate, effective viscosity and viscous flow activation energy. The melt flow index decreases with the use fire retardant fillers with a smaller average particle diameter. The melt flow rate of the polymer composition using fire retardant filler- of different chemical nature and dispersity increases with the modifier injection. For aluminum trihydroxide 2–8 times, for magnesium hydroxide 2.2–3 times, for hydromagnesite 2.0–2.2 times. The shear stress and the effective viscosity, on the contrary, decrease when the modifier is injected into the polymer composition. The obtained results allow to increase the productivity during processing of the developed materials due to the decrease of such parameters as viscosity, shear stress, increase in the melt flow parameters and shear rate. This, in turn, will positively affect the reduction of energy costs and the production time of cable products. The results will be useful in the development of formulations of polymer compositions for cable products and the directed regulation of technological parameters during their processing.